Pan-intestinal capsule endoscopy as first-line procedure in patients with suspected mid or lower gastrointestinal bleeding - Rosa, Bruno; Cúrdia Gonçalves, Tiago; Moreira, Maria J.; Dias de Castro, Francisca; Sousa-Pinto, Bernardo; Dinis-Ribeiro, Mário; Cotter, José (Endoscopy, 2024)
Background Pan-intestinal capsule endoscopy (PCE) evaluates the small bowel and colon noninvasively. This study evaluated diagnostic accuracy and safety of PCE vs. colonoscopy as first-line examination in suspected mid–lower gastrointestinal bleeding (MLGIB).Methods In this prospective, single-center, single-blinded cohort study, consecutive patients with suspected MLGIB underwent PCE followed by same-day colonoscopy. Diagnostic accuracy for potentially hemorrhagic lesions (PHLs; combined diagnosis by PCE + colonoscopy) and incidence of adverse events were assessed. Results 100 patients were included (median age 70 [range 18–92] years; 65% female). PHLs were diagnosed in 46 patients, including small-bowel and/or colon angioectasias in 32. PCE correctly identified 54 individuals without PHLs, and 95.7% (44/46) of those with PHLs vs. 50.0% (23/46) for colonoscopy (P<0.01). PHLs were detected by PCE alone in 65.2% (30/46), both examinations in 28.3% (13/46), and colonoscopy alone in 6.5% (3/46). PHLs were diagnosed at the ileocolonic region in 28% of patients, with PCE diagnosing 25/28 cases (89.3%) and colonoscopy diagnosing 23/28 (82.1%; P=0.13). Interventional procedures were performed at colonoscopy in 13/81 patients with iron-deficiency anemia (16.0%) vs. 6/19 patients with overt bleeding (31.6%; P<0.01). No significant adverse events occurred with PCE vs. 2% with colonoscopy.Conclusions In patients with MLGIB, PCE avoided further invasive procedures in >50% of patients. PCE was safe and more effective than colonoscopy in identifying PHL both in the small bowel and colon. These results support the potential use of PCE as first-line examination in patients with suspected MLGIB.